Factors affecting long-term and permanent contraceptive uptake among post-partum mothers at a hospital in Addis Ababa, Ethiopia: a cross-sectional study - Lemi Belay; Malede Birara (Elsevier, 2018)
Background: Family planning is important in reducing the total fertility rate and subsequent reduction in maternal and infant morbidity and mortality. Postnatal care represents a window of opportunity for education and communication to newly delivered mothers so that they may make appropriate choices on use of family planning. We assessed the barriers to uptake of long-term and permanent family planning methods among immediate post-partum mothers at Saint Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia. Methods: We did an institution-based cross-sectional study from Jan 1 to June 30, 2017. The 6 months of study were used as strata, with equal allocation and systematic sampling used to select participants in each month. Post-partum mothers were interviewed using pretested semi-structured questionnaires. Data entry and analysis were done using SPSS version 17. Bivariate and multivariate logistic regression were done and adjusted odds ratios (aOR), 95% CIs, and p values set at 0·05 were used to determine statistical significance of the associations. χ2 tests were used for statistical analysis of results. Findings: 422 post-partum women were interviewed, 192 (45%) of whom started long-term or permanent contraception before discharge. 268 (63%) of women had received counselling on family planning and 241 (57%) got information about contraception from the health facility. Contraceptive counselling (aOR 2·138, 95% CI 0·004-0·331, p=0·003), getting information from the health facility (15·155, 1·848-124·257, p=0·011), and partner support (1·367, 0·175-0·771, p=0·008) were associated with uptake of long-term and permanent contraception. Reasons reported for non-use were fear of side-effects (84 [40%]), opposition from husband (52 [25%]), desire to have more children, lack of awareness, and use of other methods such as lactation amenorrhoea. Interpretation: One-to-one counselling with partner involvement would ensure that mothers receive complete information from health facilities, and hence could reduce myths and misperceptions and improve uptake of long-term and permanent methods of contraception. Funding: Saint Paul's Hospital Millennium Medical College.